Ecocentric Governance: Sustainability Between the Availability of Resources and Needs - Quiroz Campas, Celia Yaneth; Carreón Guillén, Javier; Bustos-Aguayo, José Marcos; Sánchez Sánchez, Arturo; Espinoza Morales, Francisco; García Lirios, Cruz (Research and Development Agency Ministry of Home Affairs, 2022)
The objective of this study was to corroborate the dimensions of ecocentric governance: conflict between authorities and users, negotiation and agreement between the parties, and co-responsible self-regulation between the rulers and the ruled regarding energy and water resources and services. An exploratory, cross-sectional and psychometric study was carried out with a non-probabilistic selection of 100 officials and electricity and water service users. This study used the governance inventory, and the three preponderant factors were obtained: conflict, negotiation-consensus, and self-regulation-co-responsibility. The three factors refer to governance oriented towards resource conservation concerning the literature consulted. The third factor of self-regulation and co-responsibility suggests policies oriented toward the availability of energy and water resources. Empirical testing of the model in a scenario and a sample exposed to resource scarcity is recommended.